Multi-stage drying processes in Clitoria ternatea flower extracts: A method to intensify anthocyanins for botanical dye production - Nhan Kiet Tran*, Ngoc Minh Thu Trinh (Vietnam Journal of Science, Technology and Engineering, 2025)
This study presents an optimised multi-stage drying process for Clitoria ternatea (butterfly pea) flower extracts to enhance anthocyanin concentration for sustainable botanical dye production, addressing the need for nontoxic and environmentally friendly dyeing methods. This method preserves anthocyanins through pre-treatment (cleaning, alkaline stabilisation, and blanching) before a sequential drying process at 70, 60, and 50°C. Each stage gradually reduced moisture while preserving pigment stability. Anthocyanin levels were measured via UV-Vis spectrophotometry, and colour stability was tested under natural sunlight to mimic real-world conditions. The optimised protocol increased anthocyanin concentration by 40% (from 45 to 63 mg/l) while maintaining moisture content at 5-7%, ensuring long-term stability. Notably, the treated extracts retained vibrant colour under sunlight with only minor fading, proving the method’s viability for dye production. Additionally, the study introduces a scalable, eco-friendly process for producing stable anthocyanin dyes, promoting sustainable practices in textiles, cosmetics, and food production while meeting the demand for environmentally friendly alternatives.